Improving Service of Quality using Quality Function Deployment - Ratna Ekasari; Nurul Aziza; M Adhi Prasnowo; Khoirul Hidayat (Sebelas Maret Business Review, 2019)
AdiTeknik is one of the garages in Sidoarjo, East Java, Indonesia, engaged in repairing services industry tools. This garage recently has problems in attracting customers. Prior studies suggest that one of the things that affect the number of customers is customer satisfaction. After listening to complaints from several consumers, consumers said that they are less satisfied with the quality of the garage. This phenomenon become the trigger for us to investigate the customer satisfaction especially on the AdiTeknik garage. One method that can be used to help companies to improve the quality according to customer point of view is Quality Function Deployment (QFD). We find that there are twelve attributes of the desires and needs of consumers to improve the quality of garage service of AdiTeknik. Those are the quality of repair, cleanliness and neatness of the garage, complete facilities for customer, employee performance, repair results in accordance with demand, timeliness of completion, the ability to analyze problems, clarity fees and the completion time, warranty repair results, employee friendliness, ease of contacting a workshop, and a willingness to give feedback.